Are the Causes of Financial Crisis 2007-2009 Also the Determinants of Bank Performances During the Crisis: Empirical Evidence from US banks - wang, mengxi (2014)
abstract The aim of this paper is to investigate the factors influence bank industry performance. Firstly we listed the causes of financial crisis which was unbelievably virulent to the bank industry and the global economy. Secondly, the bank-specific and macro-economic determinants on bank profitability is examined using the system GMM technique to a unbalance data of US banks in New York, Chicago, Los Angeles, Philadelphia and Houston from 2005 to 2011 covered the financial crisis period. By combining the causes of financial crisis and determinants of banking profitability we find that regulations and improvement in risk estimating are more urgent and efficient than other restrictions. There is a trade-off between bank profitability and expansionary policy. We also find that endogenous money supply as well as foreign cash flows should always be monitored.